2021
DOI: 10.1111/zsc.12521
|View full text |Cite
|
Sign up to set email alerts
|

End of a mystery: Integrative approach reveals the phylogenetic position of an enigmatic Antarctic tardigrade genus Ramajendas (Tardigrada, Eutardigrada)

Abstract: is a group of microscopic segmented animals, phylogenetically related to Arthropoda and Onychophora (Jørgensen et al., 2018). Tardigrades are widely distributed in the nature, from the ocean depths to highest mountains (Nelson et al., 2018). Owing to the extreme anatomical simplicity of these animals, few morphological characters are available for the reconstruction of their phylogeny (Marley et al., 2011). This paucity of characters is especially problematic in the case of the class Eutardigrada Richters, 192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…As for previous literature by (Nelson et al, 2020), there are two endemic genera: Ramajendas (currently belonging to family Isohypsibiidae), which are found in freshwater sediment, mosses and lichens of the Antarctica and Sub-Antarctica islands. However, in the recent study proposed by (Tumanov, 2022), through the molecular phylogenetic analysis and morphological description of the Antarctic Tardigrade of genus Ramajendas, evoked the formation of a new family named Ramajendidae to place these Ramajendas species. The second monospecific genera are Acutuncus, which previously belonged to family Hypsibiidae but currently the study conducted by Vecchi et al in 2023 revealed the extension of Acutunus species into a new family named Acutuncidae based on the phylogenetic analyses and morphological studies (Vecchi et al, 2023).…”
Section: Global Distribution Of Tardigradesmentioning
confidence: 99%
“…As for previous literature by (Nelson et al, 2020), there are two endemic genera: Ramajendas (currently belonging to family Isohypsibiidae), which are found in freshwater sediment, mosses and lichens of the Antarctica and Sub-Antarctica islands. However, in the recent study proposed by (Tumanov, 2022), through the molecular phylogenetic analysis and morphological description of the Antarctic Tardigrade of genus Ramajendas, evoked the formation of a new family named Ramajendidae to place these Ramajendas species. The second monospecific genera are Acutuncus, which previously belonged to family Hypsibiidae but currently the study conducted by Vecchi et al in 2023 revealed the extension of Acutunus species into a new family named Acutuncidae based on the phylogenetic analyses and morphological studies (Vecchi et al, 2023).…”
Section: Global Distribution Of Tardigradesmentioning
confidence: 99%
“…Over the last ten years, the implementation of molecular techniques and taxonomic analyses by means of an integrative approach have accelerated the emergence of new species being characterized morphologically and genetically in detail, e.g., [5][6][7][8][9][10][11][12]. The acquisition and accumulation of genetic data tightly associated with phenotypic information enhanced studies on two major subjects in tardigrade taxonomy: (i) The recognition and disentanglement of cryptic/pseudocryptic diversity, e.g., [13][14][15][16][17][18][19] and (ii) the construction of comprehensive molecular phylogenies at the family level or higher that considerably impacted tardigrade systematics, e.g., [20][21][22][23][24][25][26][27][28][29][30]. Notably, there were not only integrative descriptions of new species for science that have contributed greatly to these subjects' investigation, but also revisional notes with updated diagnoses and new information on already-known taxa, e.g., [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%